Rise up! : the art of protest - Rippon, Jo (Charlesbridge, 2020)
"Rise up! encourages young people to engage in peaceful protest and stand up for freedom. Photographs of protest posters from the last one hundred years celebrate the ongoing fight for gender equality, civil rights, LGBT rights, refugee and immigrant rights, peace, and the environment. Includes a chapter on youth protest"--Provided by publisher.